Evaluation of an unsteady panel method for the prediction of rotor-rotor and rotor-body interactions in preliminary design - Kunze, P. (My University, 2015)
The DLR unsteady panel and free-wake code UPM is evaluated for the prediction of rotor-rotor and rotor-body interactions in preliminary design. Therefore, several well-known test cases are selected and used to compare the numerical results with experimental data. The test cases regard a tandem rotor in hover with varying rotor overlap, the performance of a tandem and a coaxial rotor in level flight and on the rotor-body interference and its effect on the rotor inflow and wake. For the proper simulation of the experiments, routines for trimming of dual rotor configurations and for the estimation of profile power were implemented. In course of the investigations, best practices for the application of UPM for interference calculations in predesign were derived, aimed at ensuring accurate results while minimizing the computational costs. Regarding the selected test cases, most of the simulation results show an excellent agreement with experimental data, both qualitatively and quantitatively. The results encourage the integration of UPM into the DLR predesign framework, enabling a physics-based consideration of many steady and unsteady interference effects in this early design stage. Nevertheless, the computational expense of the free-wake method is considerably higher compared to conventional predesign methods and exceeds a practical level for direct integration into design optimization loops. Thus, alternative approaches for the integration of UPM into the preliminary design toolchain are proposed.
Keywords: Aircraft Design